Pre-Islamic and Islamic Influences of Taman Ghairah Aceh - Muhammad Naufal Fadhil; Aji Sofiana Putri; Julie Nichols (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2022)
According to the manuscript of Bustanussalatin by Nuruddin Ar Raniry, in 1637 Sultan Iskandar Thani built a private royal garden called Taman Ghairah (Ghairah Garden). The seventeenth-century garden of Aceh still holds some questions because most of its objects are no longer found in Banda Aceh. Three buildings such as: Gunongan, Kandang and Pintô Khôp which are close to the former Sultan’s palace, are believed to be the remains of the garden. This present study is architectural research that incorporates direct observation and semiotic study on the garden simulation. The simulation is based on the Bustanussalatin manuscript. It is found that the existence of several symbols carry out meanings which relate to the influences of Islamic and pre-Islamic cultures in the past. Meru, tree of life, lotus, and banjaran sari may have derived from pre-Islamic culture, while the river, mosque and floral symbols indicate the presence of Islamic influence. This article underlines that Taman Ghairah has Islamic and Pre-Islamic cultural influences, reflecting the convergence of diverse backgrounds in Acehnese culture